Theoretical and Molecular Dynamics Simulation Approaches to Praseodymium Content Effect on Radiation Shielding and Time Dependent Volume-Collapse for a Newly Produced Borate Glass - Aygun, Murat; Aygun, Zeynep; Celik, Fatih Ahmet; Karabulut, Ezman; Yilmaz, Mucahit (Wiley-V C H Verlag Gmbh, 2024)
Gamma-ray, fast neutron and charged particle shielding characteristics of Praseodymium (Pr3+) activated glasses with composition 10ZnF2-(10-x)SrO-15Li2O-65H3BO3-xPr2O3(where x = 0.1, 0.5, 1.0, 1.5, and 2.0) are investigated. For this, the radiation shielding parameters are estimated by using Photon Shielding and Dosimetry (Phy-X/PSD), Interaction of Proton, Alpha, Gamma rays, Electrons, and X-rays with matter (PAGEX), Stopping Powers and Ranges for Electrons (ESTAR), and The Stopping and Range of Ions in Matter (SRIM) codes. Furthermore, the results are compared comprehensively and comparatively. The glasses with increasing Pr3+ content exhibited higher shielding potential. It can be said that the ZFLHBPr2.0 sample could be used as a shielding material in various applied fields. Additionally, the effect of Pr composition on structural transitions and time-dependent volume-collapse of this new family of borate glass doped with Pr is analyzed by molecular dynamics study (MD) based density functional tight binding method. The simulation results show that the addition of Pr led to the cubic-orthorhombic transformation of simulation cell at determined temperature and 1 atm pressure. Also, a sudden decrease in volume are observed within a short time at 8% Pr composition (x = 2.0) atmospheric pressure. This result provides a strong connection between Pr composition and volume change with time and at constant low pressure. The volume-collapse process with time at low pressure with adding of Pt to borate glass under low pressure shows that borate glass doped with Pt exhibits the structural evolution from cubic to orthorhombic at 8% Pr composition (x = 2.0) with time. image
Keywords: borate glass; charged particle shielding; gamma shielding; molecular dynamics; neutron shielding